(untitled) (Journal of Science and Technology, 2016)
The purpose of this study was to determine the applicability of Herzberg’s (1959) motivation-hygiene theory to clergy using fulltime stipendiary clergy in parish ministry of the Global Evangelical Church, Ghana as case study. The study involved the determination of the overall job satisfaction of clergy and the investigation of the relationship between clergy’s overall satisfaction and Herzberg, Mausner, and Snyderman’s (1959) job satisfier and dissatisfier factors. The specific job satisfier factors investigated were: achievement, recognition, work- itself, responsibility, and advancement. The job dissatisfier factors investigated were: company policy and administration, supervision, salary, interpersonal relations, and working conditions. Brayfield-Roche’s (1951) “Job Satisfaction Index” was adapted to assess the overall job satisfaction of clergy while a modified version of Wood’s (1973) “Faculty Job Satisfaction/Dissatisfaction Scale” was used to measure the satisfaction of clergy relative to Herzberg’s satisfier and dissatisfier factors. There were 117 pastors in fulltime parish ministry at the time of the survey. A total of 104 (89%) responses were returned, out of which 96 (82%) were usable. Correlation coefficients were calculated to describe the relationship between clergy’s overall job satisfaction and the job satisfier and job dissatisfier factors. The significance of the correlation coefficients were investigated by setting them against a critical alpha (significance) p=.05. Analyses of the data revealed that all the job satisfier and dissatisfier factors except “salary” were related to varying degrees to overall job satisfaction, thus implying that the basic assumptions of Herzberg, Mausner, and Snyderman’s motivational theory may not be applicable to clergy. It was also found that the “Work-itself” was the most motivating factor for clergy.